Submersibles Greatly Enhance Research on the Diversity of Deep-Reef Fishes in the Greater Caribbean - Robertson, D. Ross; Tornabene, Luke; Lardizabal, Claudia C.; Baldwin, Carole C. (Frontiers in Marine Science, 2022)
Understanding the diversity and ecology of deep-reef fishes is challenging. Due to intensive and widely dispersed sampling, the Greater Caribbean (GC) fauna of species found on shallow reefs is much better characterized than the fauna of deep-reef species restricted to mesophotic (40–130 m) and rariphotic (130–300 m) depths. Our knowledge about deep-reef fishes is based on ship-board sampling and the recent use of rebreather diving, remotely operated vehicles (ROVs), baited remote underwater videos, and crewed submersibles. Submersible research on GC deep-reef fishes began in the 1960s and has flourished over the last decade through research by the Smithsonian Institution’s Deep Reef Observation Project (DROP). Here we quantify the contribution of submersible research, particularly the surge by DROP, to our understanding of the diversity of the deep-reef fish fauna of the GC. We compared shallow- and deep-reef fish faunas of three GC sites subjected to DROP research to faunas of three sites without such research. DROP increased the size of the deep faunas at three islands ∼9-fold, and they have deep-reef faunas ∼2–4 times the size of those of the other three sites. Those deep-reef faunas have high proportions of small cryptobenthic fishes, which also represent a major component of shallow faunas. That research increased the rate of discovery (collection) of new species of deep-reef fishes ∼6-fold and accounts for 31% of the deep-reef species first discovered within the GC. Substantial numbers of new species at each of the three DROP islands were not found at the other two. This indicates that other parts of the GC likely harbor many undetected deep-reef fishes, and that the size of the deep-reef fauna of the GC is significantly underestimated. These results show that small research submersibles are versatile, highly productive tools for deep-reef studies. They allow long-duration dives at any depth, while offering unparalleled views of their surroundings to study the ecology of deep-reef fishes (e.g., DROP’s definition of the rariphotic assemblage from fish depth distributions). Submersibles can efficiently collect reef fishes of a broad range of taxa, ecotypes and sizes, leading to a more comprehensive understanding of the regional GC deep-reef fish fauna.